Development of Cluster Integration in Agricultural Sector of the Republic of Kazakhstan - Kydyrbayeva, Elmira Omirserikovna; Shomshekova, Balhiya Kulmesovna; Bisenova, Saule Shaudirbaevna; Kylyshbayeva, Bibigul Hamitovna (International Journal of Economics and Financial Issues, 2016)
This article contains an overview of the cluster approach methods, the author analyzes the existing forms of cooperation between agricultural enterprises, distinctive features of territorially-industrial clusters from other forms of organization of production in the agro-industrial complex of the Republic of Kazakhstan. We studied the experience of developed countries on the formation of the cluster system, government regulation, which allowed substantiating the necessity of formation and suggesting a mechanism of interaction between participants of geographical industrial cluster in agriculture. The main factors that justify the need for the development of cluster integration and formation of territorial and sectoral clusters in the agro-industrial complex of the Republic of Kazakhstan are studied. Keywords: Intersectorial integration, agricultural sector, economic relations, development, economic growth, industrial clusters JEL Classifications: O21, Q13, Q18